Higher military education focused on quantifiable learning outcomes - Scipanov, Lucian; BODESCU, Alin (BULLETIN OF "CAROL I" NATIONAL DEFENCE UNIVERSITY, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*500.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00658);" role="presentation">This article proposes potential solutions for adapting higher military education to the trends <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*513.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01675);" role="presentation">of education centered on learning outcomes. These solutions are based on specific military <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*526.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00744);" role="presentation">competences captured by national specialized institutions and aim to meet the requirements <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*539.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.973635);" role="presentation">of the European Qualifications Framework (EQF). The analysis and proposed model are based <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*552.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.989792);" role="presentation">on the Sectoral Qualifications Framework for the Military Officer Profession (SQF-MILOF), <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*565.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.996215);" role="presentation">which was proposed by the European Security and Defence College (ESDC) and recognized <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*578.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.986401);" role="presentation">by the Military Committee of the European Union in 2021. This approach is relevant because <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*591.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.990086);" role="presentation">the ESDC system will serve as the basis for developing a model based on learning outcomes, <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*604.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03683);" role="presentation">adapted to the national framework for training future commanders and staff officers. The <span dir="ltr" style="left: calc(var(--scale-factor)*127.56px); top: calc(var(--scale-factor)*617.87px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00556);" role="presentation">authors intend to promote this solution as one aligned with European standards.